A Study on the Stoichiometry of One-Dimensional Nanostructures - Keivan Davami; Mehrdad Shaygan; Nazli Kheirabi; Hessam Ghassemi (Advances in Condensed Matter Physics)
While attributes such as small dimensions, low power consumption, fast sensor response, and a wide range of detection give one-dimensional nanostructures excellent potential to revolutionize sensor and detector industries, challenges to achieving uniform stoichiometry pose significant obstacles to their commercial use. Diverse characteristics arise from nanostructures with variable compositions and morphologies. Thus, investigation of physical properties of nanostructures would be pointless if one cannot assure the exact stoichiometry of the material. We studied the stoichiometry of ZnTe nanowires grown via the vapor-liquid-solid method. Different microscopy and composition analysis methods were exploited to study the stoichiometry of the nanowires. It was observed that nonstoichiometric wires had relatively higher defect concentrations. The temperature profile along the substrate during nanowire growth was found to be the reason for the formation of nanowires with different stoichiometries.